2018
DOI: 10.1002/hyp.11498
|View full text |Cite
|
Sign up to set email alerts
|

A fractal analysis of the water retention curve

Abstract: The dependence of the soil water content ϑ upon the matric potential ψ is studied within a fractal approach that regards the water retention curve as a sequence of well defined fractal regimes. Each of such regimes accounts for a given functional dependence ϑ≡ϑ(ψ), which in turn is characterized by a fractal dimension. The difference between the double fractal (observed into sandy soils) and multifractal (observed into clay soils) regime is explained by recalling that, for a sandy soil, the transition from sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…This question has been (in part) positively answered by means of the fractal geometry (a general overview can be found in Hunt, Ewing, & Ghanbarian, , and references therein). In particular, the fractal approach has proven to be a valuable tool to determine the scale‐invariant exponents of the water retention curve for a large set of soils (De Bartolo, Fallico, & Severino, ). The present study aims at underlining that some remarkable properties of scale invariance of the effective water retention curve can be detected even within a stochastic approach.…”
Section: Introductionmentioning
confidence: 99%
“…This question has been (in part) positively answered by means of the fractal geometry (a general overview can be found in Hunt, Ewing, & Ghanbarian, , and references therein). In particular, the fractal approach has proven to be a valuable tool to determine the scale‐invariant exponents of the water retention curve for a large set of soils (De Bartolo, Fallico, & Severino, ). The present study aims at underlining that some remarkable properties of scale invariance of the effective water retention curve can be detected even within a stochastic approach.…”
Section: Introductionmentioning
confidence: 99%
“…S1-S3, only one changepoint occurred in the SWRC of silty loam soil, and the application of biochar did not significantly change the suction value at the changepoint. De Bartolo,Fallico, and Severino (2018) extended the model proposed by Mill an and Gonz alez-Posada (2005) and found that for sandy soil, soil water movement demonstrated double fractal regimes, whereas in clay soils, soil water movement had multifractal regimes. The experimental soil in this study was closer to sandy soil, and the hydraulic parameters could be predicted with one changepoint.…”
mentioning
confidence: 69%
“…Our approach is based on a direct scaling since analyses do not fit any specific model of . This empirical approach is well-known in literature, see for example [ 52 ] and in other contexts as to estimate the rate of sea level rise at some selected tide gauges around the world [ 53 ], in porous media [ 54 , 55 ], and in the framework of fluid mechanics [ 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%